Becoming a decolonial feminist ethnographer: Addressing the complexities of positionality and representation. Issue 3 (July 2018) - Manning, Jennifer
Organisation and management scholars are often preoccupied with developing, refining and advancing knowledge, and in so doing, the empirical process through which knowledge is advanced can be ignored together with the impact this process can have on participants and scholars. This article draws attention to how management scholars might negotiate the complexities of positionality and representation through an illustrative case: my experience of becoming a decolonial feminist ethnographer. Drawing upon my doctoral research, I share the experience of my ethnographic journey to become a decolonial feminist ethnographer. Developing a decolonial feminist approach to ethnography enabled me to identify positionality and representation as the key complexities of engaging in research with marginalised 'Others' while also providing me with the tools to address these complexities. This is not to say that becoming a decolonial feminist ethnographer is the only way to engage in research with marginalised 'Others', but this critical approach encourages researcher reflexivity and helps in addressing the issues of positionality and representation. My approach suggests an alternative way of 'seeing and doing' ethnography motivated by an ethical commitment to the participants and the desire to respect their knowledge and experiences.